Narrative. Geschichte - Mythos - Repräsentation : Beiträge des achten Berliner Arbeitskreises Junge Aegyptologie (BAJA 8) 1.12.-3.12.2017. - Backes, Burkhard; Götz, Matthieu W.; Verbovsek, Alexandra (Göttinger Orientforschungen. Ägypten., 2019)
The volume Narrative: History - Myth - Representation comprises nine contributions by international speakers that were presented and discussed at the eighth conference of the Berlin Working Group on Young Egyptology (BAJA) in December 2017. The focus of the conference was on the topic of "Narratives", which has received little attention in this form in Egyptological theory formation. The result is a wide range of contributions from different areas of Egyptology and Coptology, which are historical, cultural and visual and philological aspects. The reader can expect both a comprehensive, chronologically comprehensive introduction to the topic as well as innovative individual studies that offer insights into the current research of the subject on this interdisciplinary topic in their specific temporal and spatial contexts. The Berlin working group Junge Egyptology is a forum for young scientists that serves the exchange and presentation of new research approaches and results in Egyptology.The BAJA workshops take place regularly in the form of an open discussion round with lectures on a selected topic.